Tracing investors' minds: Investors’ inquiries and key audit matter reporting - Chen, Songsheng; Li, Chan; Sun, Lili; Zhang, Xiren (Journal of Accounting and Economics, 2026)
ABSTRACT This study investigates whether auditors incorporate investor information demand when determining key audit matter (KAM) disclosures. We measure investor information demand using a unique dataset of investor inquiries submitted through investor interactive platforms (IIPs) established by the China Securities Regulatory Commission. At the topic level, we find that auditors are more likely to disclose a given topic as a KAM when investors raise more inquiries on that topic. At the aggregate level, a higher proportion of inquiries devoted to accounting issues is associated with both a greater number of KAMs and longer KAM disclosures. Importantly, following the introduction of KAM reporting, managers’ footnote disclosures become more aligned with heightened investor inquiries, reinforcing our interpretation that the documented effects reflect auditors’ responses to investor inquiries rather than merely mirroring managerial disclosure changes. Overall, our findings suggest that auditors incorporate investor information demand into KAM disclosures.